DIETARY FIBER: DEFINTION, SOURCES AND EXTRACTION - Jolana Karovičová (Potravinarstvo, 2011)
<div style="mso-element:frame;mso-element-frame-width:498.1pt;mso-element-frame-height: 199.55pt;mso-element-frame-vspace:3.1pt;mso-element-wrap:around;mso-element-anchor-vertical: page;mso-element-anchor-horizontal:page;mso-element-left:52.45pt;mso-element-top: 55.2pt;mso-height-rule:exactly"> <p class="MsoNormal" style="text-align:justify;mso-layout-grid-align:none; text-autospace:none;border:none;mso-border-bottom-alt:solid windowtext 2.25pt; padding:0cm;mso-padding-alt:0cm 0cm 1.0pt 0cm;mso-element:frame;mso-element-frame-width: 498.1pt;mso-element-frame-height:199.55pt;mso-element-frame-vspace:3.1pt; mso-element-wrap:around;mso-element-anchor-vertical:page;mso-element-anchor-horizontal: page;mso-element-left:52.45pt;mso-element-top:55.2pt;mso-height-rule:exactly">The interest in food rich in dietary fiber increased in the recent decades, and the importance of this food constituent has led to the development of a large market for fibre-rich products and ingredients. A high dietary fiber intake has been related to several physiological and metabolic effects. By-products of plant food processing represent a major disposal problem for the industry concerned, but they are also promising sources of compounds which may be used because of their favourable technological or nutritional properties. Soluble dietary fiber is those components that are soluble in water and includes pectic substances and hydrocolloids. Good sources of soluble fibers include fruits, vegetables, legumes, soybeans, psyllium seeds and oat bran. Insoluble dietary fiber is those components that are insoluble in water and includes cellulose, hemicellulose and lignin. Whole grains are good sources of insoluble fiber. Comercialize fibre product have to perform some characteristic properties. doi:10.5219/125